Implications of endothelium dysfunction in heart failure - Wills Sanín, Beatriz (2014)
The role of the endothelium in heart failure has been the focus of intense research, since it has important biologic implications. There are individual differences in the pattern of endothelial dysfunction according to the etiology and severity of heart failure. Endothelial dysfunction is also associated with negative outcomes. We are eagerly waiting for new pharmacological agents targeted specifically to the vascular endothelium. In this review, we aim to provide a critical analysis of the available evidence on the pathological consequences and prognosis of endothelial abnormalities as related to the onset and natural history of heart failure.